2022
DOI: 10.1155/2022/5469220
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein Coupled Receptor 35 Induces Intervertebral Disc Degeneration by Mediating the Influx of Calcium Ions and Upregulating Reactive Oxygen Species

Abstract: Intervertebral disc degeneration (IDD) is a chronic disease affecting millions of patients; however, its specific etiology is unknown. G protein-coupled receptors (GPRs) are a superfamily of integral membrane receptors in cells, and the receptors respond to a diverse range of stimuli and participate in multiple cellular activities. Here, using RNA-sequencing (RNA-seq) methods and immunohistochemistry, we revealed that G protein-coupled receptor 35 (GPR35) may have a relationship with IDD. Then, we demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Prolonged exposure of cyclic mechanical tension led to DNA damage and induction of premature senescence of NP cells through the activation of the p53-p21-Rb pathway independent of oxidative stress [ 25 ]. The expression of membrane receptor G protein-coupled receptor 35 (GPR35) was higher in NP tissues from degenerated discs [ 26 ]. In NP cells, mechanical compression induced the intracellular calcium levels via GRP35 to upregulate ROS production, leading to disc cell oxidative damage [ 26 ].…”
Section: Disc Cell Senescence Under Various Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged exposure of cyclic mechanical tension led to DNA damage and induction of premature senescence of NP cells through the activation of the p53-p21-Rb pathway independent of oxidative stress [ 25 ]. The expression of membrane receptor G protein-coupled receptor 35 (GPR35) was higher in NP tissues from degenerated discs [ 26 ]. In NP cells, mechanical compression induced the intracellular calcium levels via GRP35 to upregulate ROS production, leading to disc cell oxidative damage [ 26 ].…”
Section: Disc Cell Senescence Under Various Stressorsmentioning
confidence: 99%
“…The expression of membrane receptor G protein-coupled receptor 35 (GPR35) was higher in NP tissues from degenerated discs [ 26 ]. In NP cells, mechanical compression induced the intracellular calcium levels via GRP35 to upregulate ROS production, leading to disc cell oxidative damage [ 26 ]. Ke et al reported that compression stress in human NP cells induces the Rho/ROCK1/p-MLC pathway, which induces myosin IIA interaction with actin and reduces the interaction of myosin IIB and actin.…”
Section: Disc Cell Senescence Under Various Stressorsmentioning
confidence: 99%
“…Therefore, Ager KO may have protective effect on collagen in AF. In the study of disc degeneration, a disintegrin‐like and metallopeptidase with thrombospondin type 1 motif, 5 ( Adamts5 ) KO mice used by Ngo et al, 68 cyclin dependent kinase inhibitor 2A ( Cdkn2a ) KO mice used by Che et al, 69 G protein‐coupled receptor 35 ( Gpr35 ) KO mice used by Chen et al, 70 microRNA 141 ( Mir141 ) KO mice used by Ji et al 71 and sclerostin ( Sost ) KO mice used by Kroon et al 72 were also found that the target gene they studied could exacerbate disc degeneration (Table 2 ).…”
Section: Constitutive Ko Micementioning
confidence: 99%
“…Under mechanical stress, GPR35 activation has been shown to enhance ROS production, and excessive ROS triggers further GPR35 expression ( 48 ). Conversely, GPR35 activation with Kynurenic acid in macrophages suppresses NLRP3 inflammasome activation and related inflammation by reducing mitochondrial damage and mitochondrial ROS production ( 49 ). These studies, despite showing divergent outcomes, reveal the significant role of GPR35 in modulating inflammation via ROS-mediated pathways.…”
Section: Gpr35 Involved Inflammation-related Pathwaysmentioning
confidence: 99%
“…There have been two diseases that are connected to the pro-inflammatory effects of GPR35. GPR35 plays a vital role in detecting bacteroides fragilis toxin and triggering an immune response in bacteroides fragilis toxin-induced colitis ( 89 ), and GPR35 loss in nucleus pulposus cells significantly reduces intervertebral disc degeneration typically triggered by inflammation induced by ROS or mechanical stress ( 49 ). In addition, encephalomyelitis (EAE) is worsened through the accumulation of GPR35 + /Ly6C + macrophages in the small intestine, while the blockage of KYNA-GPR35 signaling can alleviate EAE ( 75 ).…”
Section: Pro-inflammatory Roles Of Gpr35mentioning
confidence: 99%